Pengaruh Kerusakan Jalan Terhadap Kenyamanan Pengguna Jalan di Jalan Raya - Rizky Ahmad Gumelar; Adi Susetyaningsih; Muhammad Badru Zaman (Institut Teknologi Garut, 2023)
Roads are important in the distribution of goods in the industrial sector. Good roads can speed up the distribution process from one area to another. On the other hand, if the road conditions are bad, it will certainly slow down distribution in the area. Therefore, road damage conditions can affect the economic sector in the area. There are many factors that cause damaged road conditions, one of which is the volume or load of vehicles that exceeds the capacity of the road. The impact of road damage will certainly disrupt the comfort and safety of road users. This research was carried out using a survey method, directly observing the condition of road damage and distributing questionnaires to road users. Then the test is processed with Validity Test, Reliability Test, Mean Value and Standard Deviation. Based on the findings, the types of damage were Crocodile Skin Cracks, Longitudinal Cracks, Potholes and Bleeding. Then, based on the distribution of the questionnaire, all statement items are declared valid and reliable. Then, based on the mean value, it is obtained that the accident factor is the aspect that most influences the safety of road users. The road flooding factor is the aspect that has the most influence on comfort. Then the delay factor is an aspect that influences costs.